Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Variants in CAPZA2, a member of an F-actin capping complex, cause intellectual disability and developmental delay. - Huang, Yan; Mao, Xiao; van Jaarsveld, Richard H; Shu, Li; Terhal, Paulien A; Jia, Zhengjun; Xi, Hui; Peng, Ying; Yan, Huiming; Yuan, Shan; Li, Qibin; Wang, Hua; et al. (Hum Mol Genet, 2020)
The actin cytoskeleton is regulated by many proteins including capping proteins that stabilize actin filaments (F-actin) by inhibiting actin polymerization and depolymerization. Here, we report two pediatric probands who carry damaging heterozygous de novo mutations in CAPZA2 (HGNC: 1490) and exhibit neurological symptoms with shared phenotypes including global motor development delay, speech delay, intellectual disability, hypotonia and a history of seizures. CAPZA2 encodes a subunit of an F-actin-capping protein complex (CapZ). CapZ is an obligate heterodimer consisting of α and β heterodimer conserved from yeast to human. Vertebrate genomes contain three α subunits encoded by three different genes and CAPZA2 encodes the α2 subunit. The single orthologue of CAPZA genes in Drosophila is cpa. Loss of cpa leads to lethality in early development and expression of the human reference; CAPZA2 rescues this lethality. However, the two CAPZA2 variants identified in the probands rescue this lethality at lower efficiency than the reference. Moreover, expression of the CAPZA2 variants affects bristle morphogenesis, a process that requires extensive actin polymerization and bundling during development. Taken together, our findings suggest that variants in CAPZA2 lead to a non-syndromic neurodevelopmental disorder in children.